Masjid Sultan Ismail UTM Sekudai, Johor [fotograf] - Universiti Teknologi Malaysia
DYMM Sultanah Johor - Raja Tun Mohar bin Raja Badiozaman, Prp Canselor UTM (1983 - 1992) - Dato' Prof Muhammad Ridzuan bin Hj Mohd Salleh - Datuk Prof Dr Mohammad Noor bin Haji Salleh